Kualitas Layanan dan Kepuasan Pelanggan: Studi Eksplorasi atas Atribut Kualitas Layanan pada Fakultas Ekonomi Universitas Wijaya Kusuma Surabaya - Kristiningsih Kristiningsih; Adrianto Trimarjono (Jurnal Maksipreneur, 2019)
The purpose of this study was developing a service quality model in the business of higher education services at the Faculty of Economics, University of Wijaya Kusuma Surabaya, Indonesia which is grounded that can be used as the foundation of researchers in a service research and implementation for business practitioners of higher education services. This research used a qualitative research design with a critical incident technique model, which explored the answers of the student respon-dents and alumni service users to examine deeper the experience of understanding the most satisfying and the most unsatisfaction of institutions.